ENT 530 : Case Study: Love Dessert / Emirul Afiq Eddy Akmar ... [et al.] - Eddy Akmar, Emirul Afiq; Mazilan, Muhammad Fitri; Nazlimen, Nurul Aqilah; Warna Hari, Nurul Hanani; Sabihan, Rabiatul Anisah (2021)
By doing this case study, we will find out precisely about the company’s overview, analysis and problems that we will discuss on how to solve them. The method that we use to interview Puan Aishah who is the owner of the business we choose is by online live meeting. We choose to use Google Meet as it is simple and easy to use, and it is also agreed by Puan Aishah. During this pandemic of Covid-19, we are obligated by government to stay at home in order to avoid further spread of the virus. Puan Aishah started her business out of her interest in baking and she named her business, Love Desserts. The name ‘Love Desserts’ literally defined as her products are for the ones who admire and love to eat desserts. This name is good for her type of business as it is very straightforward. People could know right away what she is selling for her business. She started her business in 2015 when she was just making desserts for her friends as a hobby, but her friends eventually encouraged her to start scrutinizing this hobby and turn it into a beneficial and profitable task. Love Desserts serves variety of dessert such as birthday cakes, muffins, puffs, Malaysian traditional sweet treats and pastries. All products are deemed to be safe to consume and made with all Halal ingredients that Puan Aishah herself picked up from her nearest supermarket.